Research on ESG performance and financial performance of new energy enterprises - Xu, Siqi (International Journal of Global Economics and Management, 2024)
ESG is more about measuring corporate environment, social responsibility, and corporate governance than traditional financial data considerations. For the long-term development of globalization and dual-carbon strategy, based on sustainable development and the realization of global development, many enterprises will consider ESG performance in corporate financial performance evaluation. In the era of advocating green life, new energy enterprises have received much attention, but their industry financial performance is closely related to ESG performance. This paper takes all of China’s A-share-listed new energy companies from 2010 to 2021 as the research object and verifies the relationship between ESG performance and financial performance of new energy enterprises through empirical analysis, which is of great significance for better high-quality development of new energy enterprises.